The Use of Mobile Assisted Language Learning in English Learning of Fourth Semester English Department Students at IAIN Samarinda - Anis Hidayah Nafa (Jurnal Tarbiyah dan Ilmu Keguruan Borneo, 2021)
Mobile Assisted Languge Learning, (MALL,) is a learning tool  focused on language learning that used  mobile phone. MALL in English learning is handy for students who in need to enhancing their English skills. Especially English department students at IAIN Samarinda, they were required to master the primary English language skill to support the learning process. The research objective was to knew students perspective toward the use of MALL in English learning, how do studnets use MALL to support their English learning activities in English and their perpective toward the advantages and disadvantages of utilizing MALL. The instrument was interview conducted by a brief introduction to the subject of the study and then selected students based on their last GPA. Based on the data finding, MALL are indeed useful and bring advantages for students. They share their experience in using MALL for English learning to facilitate, save time and energy, easy theory learning and information access, and improve motivation. However, besides the advantages MALL can provide, it also has its disadvantages. The students shared that the mobile phone is too small so that it is difficult to type, the application of online classes is not yet perfect, the source of material that cannot be trusted completely and the difficulty of internet access that requires money is limited for some students